METHOD OF THERMAL RECYCLING OF BIOMASS USING A HELIOPYROLISIS DEVICE - Almardanov , Hamidilla Abdiganievich (Educational Research in Universal Sciences, 2023)
The article analyzes the thermal performance of insolation passive solar heating systems and the results of scientific research. The developed systems, advantages and disadvantages of thermal engineering methods of their calculations are presented. The goals of the computational and theoretical studies of the type of solar heating systems under consideration are aimed at an approximate assessment, without taking into account their thermal efficiency, the degree of optimization of individual elements of the system, as well as thermal parameters.